Exposure-safety relationship for acyclovir in the treatment of neonatal herpes simplex virus disease. (July 2022) - Ericson, Jessica E.; Benjamin, Daniel K.; Boakye-Agyeman, Felix; Balevic, Stephen J.; Cotten, C. Michael; Adler-Shohet, Felice; Laughon, Matthew; Poindexter, Brenda; Harper, Barrie; Payne, Elizabeth H.; Kaneshige, Kim; Smith, P. Brian; et al.
Abstract: Background: Neonatal herpes simplex virus (HSV) disease has been treated with high-dose (20 mg/kg/dose) acyclovir since 1991. Aims: Determine the safety of acyclovir in infants with neonatal HSV treated with high-dose acyclovir; examine the association between acyclovir dose and exposure with adverse events (AEs). Study design: We obtained demographic information and acyclovir dosing via medical records. Acyclovir exposure was calculated using an established pharmacokinetic model. Subjects: Infants <120 days of age with neonatal HSV discharged from four academic children's hospitals. Outcome measures: We identified clinical and laboratory adverse events (AEs). Results and conclusions: We identified 49 infants with neonatal HSV treated with acyclovir; 42 infants had complete 21-day dosing information. Median mean daily dose was 59 mg/kg/day. Clinical AEs were common among all gestational and postnatal age groups. Rash was the most common clinical AE (37 %). Mild laboratory AEs occurred in 2–37 % of infants. The median maximum doses (mg/kg/day) were higher among infants with hypokalemia, elevated blood urea nitrogen, and thrombocytosis. For all other laboratory AEs, the median maximum doses for infants without events were higher or equal to the median maximum dose of infants with the AE. The odds of experiencing any clinical or laboratory AE did not differ by predicted acyclovir exposure for either area under the curve (AUC) or maximum concentration (Cmax) (odds ratio [OR] = 1.00 [0.98, 1.03] and OR = 1.01 [0.93, 1.12], respectively). Although AEs were common with high-dose acyclovir exposure, severe AEs were rare. Acyclovir exposure was not associated with AEs. Highlights: Linking acyclovir exposure to safety in infants has not been previously reported. Although AEs were common with high-dose acyclovir use, severe AEs were rare. Acyclovir exposure was not associated with the incidence of AEs.